Sport Massage for Lower Back Pain (Study of Treatment Model Development for Sports Health) - Surya Adi Saputra; Ari Wibowo Kurniawan; Supriyadi Supriyadi (Inspiree)
The purpose of the study. The purpose of this research is to create a model of the Sports Massage program by application, specifically for sufferers of Lower Back Pain. the novelty of this product is: the sports massage program model is usually only given to athletes for recovery, but this time the sports massage is made specifically for the treatment of lower back pain sufferers.